A latent class analysis of tailored substance use treatment programs: Implications for treating syndemic conditions facing sexual and gender minority populations. (1st September 2022) - Helminen, Emily C.; Cascalheira, Cory J.; Shaw, Thomas J.; Zollweg, Sarah; Hughes, Tonda L.; Scheer, Jillian R.
Abstract: Background: Syndemics (i.e., multiple, co-occurring, and synergistic conditions) contribute to elevated substance use among sexual and gender minority (SGM) people relative to heterosexual, cisgender people. Research suggests that syndemic-informed and SGM-tailored treatments are effective in substance use treatment among SGM people. However, few studies have examined 1) the proportion of substance use treatment facilities offering syndemic-informed, SGM-tailored treatment programming; and 2) the availability and accessibility of syndemic-informed, SGM-tailored treatment programs across the U.S. Methods: We used the 2020 National Survey of Substance Abuse Treatment Services (N-SSATS) dataset to perform a latent class analysis examining whether substance use treatment facilities' tailored treatment programs cluster together to form distinct classes indicating whether facilities offer syndemic-informed and SGM-tailored programming. We then used multinomial logistic regression to examine associations between class membership and facility availability and accessibility. Results: Analyses revealed four classes of substance use treatment facilities' tailored programs. Facilities with syndemic-informed and SGM-tailored treatment programs compared to facilities with no tailored programs were more likely to be in the Northeast compared to the Midwest and South; to offer payment assistance versus not offer payment assistance; and to be private, for-profit facilities versus public or non-profit facilities. Conclusions: This study's findings identify the need for more facilities with syndemic-informed and SGM-tailored treatment, particularly in the Midwestern and Southern U.S. regions. Facilities offering syndemic-informed and SGM-tailored treatment might present accessibility barriers for low-income SGM people, as they were more likely to be private, for-profit facilities; however, they were more likely to offer payment assistance. Highlights: Latent class analysis revealed four classes of facilities' tailored programs. Only one class (Class 3) offered programming relevant to syndemics among SGM people. Facilities in Class 3 were underrepresented in the Midwest and Southern U.S. Facilities in Class 3 were more likely to private, non-profits rather than public. Facilities in Class 3 were more likely to offer payment assistance.